2022
DOI: 10.21203/rs.3.rs-2142200/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cuproptosis-related lncRNA signature for predicting prognosis and immune response in hepatocellular carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) has a high incidence and poor prognosis. Cuproptosis is a novel type of cell death, which differs from previously reported types of cell death such as apoptosis, autophagy, proptosis, ferroptosis, necroptosis, etc. Long non-coding RNAs (lncRNAs) play multiple roles in HCC. To improve the prognosis of HCC, it is necessary to construct a signature using cuproptosis-related lncRNAs. Methods: We downloaded information including RNA-seq transcriptome, clinical data and sim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…5B). The immunophenotype score (IPS) scoring system is now widely used to assess tumor responsiveness to immunotherapy [25]. The results of the analysis demonstrated that patients with high expression of PXDN had higher IPS scores regardless of PD1 and CTLA4 positivity or negativity (Fig.…”
Section: Pxdn Expression Levels Affect Sensitivity To Chemotherapy Sm...mentioning
confidence: 99%
“…5B). The immunophenotype score (IPS) scoring system is now widely used to assess tumor responsiveness to immunotherapy [25]. The results of the analysis demonstrated that patients with high expression of PXDN had higher IPS scores regardless of PD1 and CTLA4 positivity or negativity (Fig.…”
Section: Pxdn Expression Levels Affect Sensitivity To Chemotherapy Sm...mentioning
confidence: 99%
“…(Figure 2C). [12][13][14][15][16][17] To further validate the clinical significance of LLPSI, we analysed the association between LLPSI and different clinical traits and found that LLPSI was significantly associated with patients' Stage and Tstage (Figure 2D). We evaluated the area under the curve (AUC) values and showed that LLPSI had high accuracy in predicting 1-, 3-and 5-year survival in patients with HCC (Figure 2E).…”
Section: External Dataset Validation and Clinical Relevance Of Llpsimentioning
confidence: 99%